HAPLOIDENTICAL TRANSPLANT WITH POST-TRANSPLANT CYCLOPHOSPHAMIDE FOR ACUTE MYELOID LEUKAEMIA AND MYELODYSPLASTIC SYNDROMES PATIENTS: THE ROLE OF PREVIOUS LINES OF THERAPY. - Daniele Avenoso; Fabio Serpenti; Liron Barnea Slonim; Styliani Bouziana; Francesco Dazzi; Guy Hannah; Michelle Kenyon; Varun Mehra; Austin Kulasekararaj; Pramila Krishnamurthy; Mili Naresh Shah; Sharon Lionel; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Allogeneic haematopoietic stem-cell transplant is a potentially curative option for high-risk acute myeloid leukaemia (AML) and myelodysplastic syndrome (MDS) patients. Post-transplant cyclophosphamide administration allows for selection of haploidentical donors in patients who are eligible for the procedure, but do not have a fully matched donor, since it can overcome the HLA barrier. There is still an active debate on whether intensification of the conditioning regimen is necessary with haploidentical donors when peripheral blood stem cells are used as the source of the graft.